The Impact of Physical Distribution Service Quality, Price and Brand Image on JNE Customer Satisfaction - Susilawati, Digita; Pebrianti, Priskila Dwi; Marina, Sandriana; Suminar, Ratna (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2023)
The rapid increase in online business has resulted in greater expanded delivery services that ease consumers to deliver goods. Due to the large number of delivery service companies, competition is getting tougher. Therefore, companies need to satisfy their customers. This study aims to determine the influence of physical distribution service quality, price, and brand image on customer satisfaction with JNE courier service. This study employed a convenience sampling method for collecting data from 124 respondents who had used the courier service surveyed to test three hypothesized relationships among the constructs of physical distribution service quality, price, and brand image on customer satisfaction using variance-based structural equation modeling (PLS-SEM). The findings of this study showed that physical distribution service quality, price, and brand image have a positive effect on customer satisfaction.